The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1155/2015/531231
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dependence of Physical Attributes and Mechanical Properties of Ultisol in a Sugarcane Field

Abstract: This study investigates the effect of conventional tillage and application of the monoculture of sugar cane on soil health. Variables like density, moisture, texture, consistency limits, and preconsolidation stress were taken as indicators of soil quality. The measurements were made at a 120 × 120 m field cropped with sugar cane under conventional tillage. The objective of this work was to characterize the soil and to study the spatial dependence of the physical and mechanical attributes. Then, undisturbed soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…According to Rossetto et al (2010), sugarcane monoculture leads to biodiversity loss and affects local and regional fauna and flora. Furthermore, soil tillage is traditionally with use of various agricultural machinery mainly made with disc plows, dish harrows and subsoilers (Portilho et al, 2011;Tavares et al, 2015;Surendran et al, 2016) that negatively affect soil aggregation and reduce biological activity (Benito et al, 2008). In addition to modifying soil physico-chemical characteristics, sugarcane cultivation also produces environmental chemical contamination and soil compaction (Iwai et al, 2008;Nurhidayati et al, 2012;Siqueira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to Rossetto et al (2010), sugarcane monoculture leads to biodiversity loss and affects local and regional fauna and flora. Furthermore, soil tillage is traditionally with use of various agricultural machinery mainly made with disc plows, dish harrows and subsoilers (Portilho et al, 2011;Tavares et al, 2015;Surendran et al, 2016) that negatively affect soil aggregation and reduce biological activity (Benito et al, 2008). In addition to modifying soil physico-chemical characteristics, sugarcane cultivation also produces environmental chemical contamination and soil compaction (Iwai et al, 2008;Nurhidayati et al, 2012;Siqueira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…So, these machines must apply pressures to the soil between 275 and 172 kPa in the friability region (0.19-0.31 kg kg −1 ), respectively, to avoid soil compaction. Reference [15], evaluating preconsolidation pressure in Acrisol under sugarcane cultivation, concluded that the load limit machines apply, aiming to remain within the soil support capacity, 126.28 kPa for a moisture content of 0.10 kg kg −1 or >75.70 kPa for moisture of 0.19 kg kg −1 .…”
Section: Comparison Of Models Between Layers Within the Managementmentioning
confidence: 99%
“…This indicates that specific management regions of σ p may be monitored by soil water content and σ p mapping enables the identification of management limits. Reference [15] also found spatial variability structure in sugarcane soil and highlighted that preconsolidation stress maps may indicate areas that support heavier equipment and areas that can tolerate only lighter vehicles before further compaction occurs. Soil compaction susceptibility becomes critical under excess water in the soil, reducing its load-bearing capacity [7,10,15,20].…”
Section: Spatial Variability Of Preconsolidation Pressurementioning
confidence: 99%
See 1 more Smart Citation